2018
DOI: 10.3390/mti2040066
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Study Approach to Explore the Effect of User Characteristics on Users’ Perception and Evaluation of a Virtual Assistant’s Appearance

Abstract: This research investigates the effect of different user characteristics on the perception and evaluation of an agent's appearance variables. Therefore, two different experiments have been conducted. In a 3 × 3 × 5 within-subjects design (Study 1; N = 59), three different target groups (students, elderly, and cognitively impaired people) evaluated 30 different agent appearances that varied in species (human, animal, and robot) and realism (high detail, low detail, stylized shades, stylized proportion, and styli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Because of the Wizard-of-Oz setting, the agent responded with higher accuracy than current state-of-the-art agents, which might affect the evaluation and responses toward the agent. Although the quick responses of the wizard might match the expectations participants had of the humanoid agent, when these expectations are not fulfilled in real application, people might lose interest to interact with the agent [14]. Thus, further long-term and field studies are needed to support the current findings and to derive better insights for possible design guidelines.…”
Section: Summary and Interpretationmentioning
confidence: 78%
See 3 more Smart Citations
“…Because of the Wizard-of-Oz setting, the agent responded with higher accuracy than current state-of-the-art agents, which might affect the evaluation and responses toward the agent. Although the quick responses of the wizard might match the expectations participants had of the humanoid agent, when these expectations are not fulfilled in real application, people might lose interest to interact with the agent [14]. Thus, further long-term and field studies are needed to support the current findings and to derive better insights for possible design guidelines.…”
Section: Summary and Interpretationmentioning
confidence: 78%
“…As virtual assistance is applied in health-related domains in this research, the results of Straßmann and Krämer [13] might be better applicable. Further research [14] complements the assumptions and demonstrates that the species is more important in the evaluation process of a virtual agent's appearance for seniors and that seniors evaluate machine-like agents less positively than humanoid ones. Based on these features, for seniors, no differences between different degrees of realism are assumed, whereas they are expected to evaluate a humanoid agent more positively.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In [15], for instance, species and realism are identified as the key variables of agent appearance. The research indicates different species (human, animal, robots, objects, and mystical creatures) and realism levels (stylization, resolution, and detailedness) which, in later work by the same authors, was demonstrated to have an impact on older people's willingness to interact with an agent [16,17].…”
Section: Experimental Designmentioning
confidence: 90%